1997
DOI: 10.1002/(sici)1097-4695(19970620)32:7<695::aid-neu5>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Drosophila eye‐specific diacylgylcerol kinase, rdgA , which is essential for the maintenance of the photoreceptor

Abstract: The Drosophila retinal degeneration A (rdgA) mutant has photoreceptor cells that degenerate within a week after eclosion. The degeneration starts with the disruption of the subrhabdomeric cisternae (SRC), which are the organelles essential for the transport of phospholipids to the photoreceptive membranes. Our previous biochemical and molecular studies suggested that the rdgA gene encodes an eye‐specific diacylglycerol kinase (DGK). In this study, we show that retinal degeneration is prevented by the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…They found a mutation in the ATP binding site that would presumably account for the loss of DGK activity. This group later showed that the rdgA phenotype could be rescued by introducing wild-type rdgA into the mutant strain (64). Together, these studies demonstrate that formation of phosphatidic acid by dDGK2 is necessary for proper visual signaling in Drosophila.…”
Section: Function(s) Of Dgksmentioning
confidence: 86%
“…They found a mutation in the ATP binding site that would presumably account for the loss of DGK activity. This group later showed that the rdgA phenotype could be rescued by introducing wild-type rdgA into the mutant strain (64). Together, these studies demonstrate that formation of phosphatidic acid by dDGK2 is necessary for proper visual signaling in Drosophila.…”
Section: Function(s) Of Dgksmentioning
confidence: 86%
“…Drosophila chaoptin mutants display remarkable membrane abnormalities (49). The protein encoded by retinal degeneration A (rdgA) is associated with the transport of phospholipids to the photoreceptive membranes, and the Drosophila rdgA mutant induces degeneration in photoreceptor cells within a week posteclosion (50). Down-regulation of both chaoptic and rdgA at the protein level suggests disruption of the structural integrity of neuronal cell membranes that could lead to failure in cell communications and subsequent malfunction of cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Th e second-instar larvae were dissected between the A6 and A7 segments, fi xed with 4 % paraformaldehyde and 1 % glutaraldehyde in cacodylate buff er (pH 7.4) 39 , and observed by transmission electron microscopy 40 .…”
Section: Rnai In Drosophilamentioning
confidence: 99%